Pergeseran Makna Istilah Bahasa Inggris Dalam Bahasa Gaul Generasi Z Pada Platform Tiktok: Kajian Semantik - Novita Salwa Pratiwi Yamin; Mohamad Bahrul Ulum Safar; Emil Hardiansyah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The rapid development of digital communication has contributed to the emergence of various linguistic innovations among Generation Z, particularly through social media platforms such as TikTok. One of the prominent phenomena is the use of English terms that undergo semantic shifts when adopted into Indonesian youth slang. This study aims to describe English terms that experience semantic change in Generation Z slang on TikTok, identify the forms of semantic shifts, and explain the factors underlying such changes. This research employed a qualitative descriptive approach. The data consisted of words, phrases, captions, comments, and utterances containing English terms used by Generation Z in TikTok content. Data were collected through documentation and observation techniques and analyzed using data reduction, data presentation, and conclusion drawing procedures. The findings revealed 20 English terms, consisting of 12 words and 8 phrases, that experienced semantic shifts. The identified forms of semantic change include semantic broadening, semantic narrowing, association, metaphor, and amelioration. Metaphor was found to be the most dominant type of semantic shift, followed by semantic broadening and association. These findings indicate that Generation Z actively reconstructs the meanings of English terms according to the communicative needs and cultural practices of digital environments. The study contributes to semantic studies by demonstrating how social media functions as a space for the creation and dissemination of new meanings in contemporary digital communication.